Using of geochemical methods for the detection of environmentally unfavourable zones; Metals in the Environment - Rikhvanov L. P. Leonid Petrovich; Yazikov Y. G. Yegor (Egor) Grigoryevich; Baranovskaya N. V. Nataliya Vladimirovna; Belyaeva A. M.; Arkhangelskaya T. A. Tatyana Aleksandrovna; Shatilov A.Yu.; Berchuk V. V.; Talovskaya A. V. Anna Valerievna; Iankovitch E. P. (2007, 2007)
В фонде НТБ ТПУ отсутствует